Recent advances in the elimination of persistent organic pollutants by photocatalysis - Gaur, Nisha; Dutta, Dhiraj; Singh, Ayushi; Dubey, Rama; Kamboj, Dev Vrat (Frontiers in Environmental Science, 2022)
The non-ending needs of growing human population are being met by rapid industrialization and globalization which have nowadays becomes an indispensable component of growth. Although these activities have led to the gigantic growth of the human civilization but at the same time have resulted into severe environmental pollution by discharge of highly toxic waste. This waste is severely detrimental not only for the environment but also for the health of human population. Among different classes of pollutants, one being considered as one of the highly toxic ones is that of persistent organic pollutants (POPs). Advance Oxidation Technologies (AOTs) play a major role in the degradation of the pollutant by converting organic pollutants into CO2, H2O, and mineralized inorganic ions. AOTs include such as UV-based photocatalysis, ozonation, electrochemical oxidation, Fenton and Fenton-like processes, etc. There are some difficulties and challenges associated with the AOT such as high capital intensive, high energy consumption, etc. To overcome these bottlenecks, the photocatalytic degradation is a promising method that utilizes solar energy for the degradation of such pollutants. Photocatalysis is further classified into homogenous and heterogenous photocatalysis. In heterogenous photocatalysis, semiconductor photocatalyst got great attention but because of the drawbacks such as the recombination of the electron/hole pair, low adsorption rate, low surface area coverage nanotechnology got consideration for bringing novel and enhanced remediation photocatalysis process. To this end, the designing of the more efficient photocatalyst by varying morphology, composition, structure, reducing toxicity, etc is a need of an hour for the abatement of the environmental pollutants. This review focuses on the degradation and removal of the highly toxic persistent organic pollutant by utilization of photocatalytic degradation with a detailed account of the various pollutants, their degradation mechanism, process shortcomings, remedial measures, and future prospects.